Place Branding – Geographical Approach. Case Study: Waterloo - Marius-Cristian Neacşu; Silviu Neguţ; Gheorghe Vlăsceanu (Amfiteatru Economic)
This study represents an exploratory analysis of the evolution of the place branding concept, with an important focus on the geographical perspective. How has this notion, a newcomer into the geographers' analysis, changed over time and what role does it have in the decision making process of intervening into the way a certain place is organised or as an instrument of economic revival and territorial development? At least from the perspective of Romanian geographical literature, the originality and novelty of this study is obvious. An element of the originality of this research is the attempt of redefining the concept of place branding so that it is more meaningful from the perspective of spatial analyses. The reason for which Waterloo was chosen as a case study is multi-dimensional: the case studies so far have mainly focused on large cities (urban branding instead of place branding) and this site has all the theoretical elements to create a stand-alone brand.